Characteristics of femur fracture patients at Sanjiwani general hospital Gianyar in 2019 - Dwipayana, Anak Agung Ngurah Krisna; Premana, Kadek Yoga; Wisnawan, I. Made Yedi (International Journal of Research in Medical Sciences, 2021)
Background: Fracture is a discontinuity of bone which is often followed by damage to the surrounding soft tissue, such as blood vessels, muscles, and nerves. World health organization (WHO) stated that there are 5.6 million people died due to fractures and 1.3 million people suffering fractures due to traffic accidents in 2011-2012. One of the most common fractures on lower extremities due to severe trauma is femur fracture. Femur fracture is usually caused by trauma due to pressure that exceeds the capacity of the femur. Femur fracture today is still common and remains one of the major challenges for orthopaedists. Although management in orthopaedic had been growing rapidly, the one-year mortality rate post-trauma is still high, about 10-20%. This study aims to determine the characteristic of femur fracture patients at Sanjiwani hospital Gianyar in 2019. Methods: This study is a retrospective descriptive study that aims to identify the characteristic of femur fracture patients at Sanjiwani hospital Gianyar in 2019. The samples of this study were collected using total sampling technique. The data was obtained from medical record of patients diagnosed with femur fracture at Sanjiwani hospital Gianyar during January-December 2019. Variables in this study including age, sex, cause of femur fractures, type of fractures, and location of the fractures. All obtained data will be analysed using SPSS statistics 22 software. Results The result of this study showed that most of samples are male with 26 peoples (61.9%) and age group is 21-30 years old is the most common age group with 11 peoples (26.2%). Close fracture is the most common fracture type with 38 peoples (90.5%) and located in the middle shaft of femur with 20 peoples (47.6%). Conclusions: In conclusion, the most common characteristic of femur fracture patients at Sanjiwani hospital Gianyar in 2019 is male, age 21-30 years old, closed fracture and located in the middle shaft of the femur.